Modification of the method for spectrophotometric determination of chromium in waste waters by diphenylcarbazide - Stafilov, Trajče (Macedonian Journal of Ecology and Environment, 1994)
A correction and addition of the spectrophotometric method for chromium determination by diphenylcarbazide was proposed. The changes made refer to waste water samples containing Fe, Ni and Mn in high concentration. The maximum concentrations of Fe, Ni and Mn, which have no interference to the Cr determination, are 50,1000 and 1000 mg*cm-3, respectively. By precipitation and removing of these elements it is possible to determine the Cr content in such types of waste waters without problems. The oxidation of Cr(III) to Cr(VI) is very effective.